IMPLIKASI PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP BAHASA ANAK DI MIS AL-KHAIRAAT POMBEWE - Hilmawati Hilmawati; Ahmad Syahid; Rizka Fadliah Nur; M. Iksan Kahar; A. Ardiansyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The widespread use of TikTok among elementary school students has brought noticeable changes to the way children communicate in their daily lives. The platform is no longer used merely as a source of digital entertainment, but has also begun to shape students’ word choices, speaking styles, and language habits. This condition can be observed among students at MIS Al-Khairaat Pombewe, who have become increasingly familiar with viral expressions, popular abbreviations, slang, and the mixing of Indonesian with foreign languages in everyday conversations. Such circumstances have raised concerns regarding the declining use of proper and standard Indonesian within the school environment. This study employed a descriptive qualitative approach involving the principal, teachers, and students selected purposively as research informants. Data were collected through observations, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that TikTok exerts a dual influence on children’s language development. On the one hand, the platform contributes to vocabulary expansion, enhances students’ creativity in language use, and broadens their digital knowledge. On the other hand, the intensity of TikTok usage encourages the frequent use of informal language in formal situations, leading to a gradual decline in the use of proper Indonesian according to linguistic norms. Therefore, the involvement of teachers and parents is necessary to guide children toward wiser social media use without neglecting the development of their language abilities. ABSTRAK Fenomena penggunaan TikTok di lingkungan sekolah dasar memperlihatkan perubahan yang cukup nyata pada cara siswa berkomunikasi sehari-hari. Platform ini tidak lagi sekadar dimanfaatkan sebagai hiburan digital, tetapi turut membentuk pilihan kata, gaya berbicara, hingga kebiasaan berbahasa anak. Kondisi tersebut terlihat pada siswa MIS Al-Khairaat Pombewe yang semakin akrab dengan istilah viral, singkatan populer, bahasa gaul, serta pencampuran bahasa Indonesia dengan bahasa asing dalam percakapan mereka. Situasi ini memunculkan perhatian terhadap menurunnya penggunaan bahasa Indonesia yang baik dan benar di lingkungan sekolah. Kajian ini memanfaatkan pendekatan deskriptif kualitatif dengan melibatkan kepala sekolah, guru, dan siswa sebagai informan yang dipilih secara purposive. Informasi penelitian diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian dipahami melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian memperlihatkan bahwa TikTok memberi pengaruh ganda terhadap perkembangan bahasa anak. Di satu sisi, media sosial tersebut membantu siswa memperluas kosakata, meningkatkan kreativitas dalam berbahasa, dan memperkaya wawasan digital mereka. Di sisi lain, intensitas penggunaan TikTok ikut mendorong penggunaan bahasa informal dalam situasi formal sehingga kebiasaan menggunakan bahasa Indonesia sesuai kaidah menjadi semakin berkurang. Karena itu, keterlibatan guru dan orang tua dibutuhkan agar penggunaan media sosial dapat diarahkan secara lebih bijak tanpa mengabaikan perkembangan kemampuan berbahasa siswa.